THE INFLUENCE OF COMMERCIAL ACTIVITIES ON RESIDENTIAL HOUSES IN PATUK VILLAGE ON THE ARCHITECTURAL FORM AND CULTURE OF THE COMMUNITY - Prakosa, Prakosa; Primi Artiningrum (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
The development of tourism in the Pleret-Patuk corridor, Gunungkidul Regency, has led to the conversion of residential houses into commercial spaces, which has impacted the architectural form and cultural dynamics of the local community. These changes are not only physical, but also relate to how the community negotiates economic needs with long-established local cultural values. This study aims to analyze the influence of commercial activities on the transformation of residential architecture and its implications for cultural values and social interaction patterns in Patuk Village. This study uses a qualitative approach with a case study strategy. Data were collected through in-depth interviews, field observations, and visual documentation of 15 residential houses that have undergone a change in function to commercial spaces. The analysis focused on changes in physical building elements based on the classification of fixed, semi-fixed, and non-fixed elements, as well as their relationship with the spatial patterns and social relations of the occupants. The results of the study show that non-fixed and semi-fixed elements underwent the most significant changes, especially on the facade, openings, and layout of the front of the house. Meanwhile, fixed elements tended to be retained to maintain the identity of the building and the continuity of cultural values. The front area of the house is the most flexible area for commercial activities, while the private zone is maintained. The architectural transformation still reflects local cultural values through the use of materials, decorations, and business practices based on local wisdom. These findings show that adapting residential houses can be a sustainable strategy in meeting the economic needs of the community without losing local cultural identity.